Power relations through the prism of critical discourse analysis and systemic functional grammar - Avdagić Kemal; Džanić Mirza (ExELL (Explorations in English Language and Linguistics))
The paper aims to evaluate the role of language in a specific socio-political context. It offers a critical approach and evaluation of the political statements of the European Union representatives regarding the process of the accession of Bosnia and Hercegovina to the European Union. The focus of the linguistic investigation is on the identification of language structures that participate in the development of communicative models that enable the establishment of power relations between participating entities. The linguistic data is obtained through systemic functional grammar and evaluated using critical discourse analysis.